META ANALYSIS EFFECT NATURAL SCIENCE OF MODULE WITH CONNECTED MODELS ON THE LEARNING OUTCOMES OF JUNIOR HIGH SCHOOL STUDENT - Annisa Rahmi; Asrizal Asrizal; Amali Putra; Wahyuni Satria Dewi (Universitas Negeri Padang, 2022)
Education in the 21st century is one of the characteristics of the era of globalization with the development of Science and Technology. 21st century learning really expects integrated science learning that can be packaged into one between chemistry, physics and biology learning materials. The purpose of this study was to determine the effect size and summary effect size of the use of integrated science modules with connected models based on four categories, namely grade level, learning materials, connected models and learning outcomes. The solution to overcome this problem is to conduct a meta-analysis of the effect of integrated science modules with connected models in science learning on junior high school students' knowledge. The research data consists of 10 national and 1 international articles and 9 theses. The data analysis technique in this study uses the calculation of the effect size in each article and the calculation of the summary effect size. Based on the data analysis, three results of this study can be stated. First, the effect size obtained on student learning outcomes vary. Second, the influence of integrated science modules with connected models at the level of class VII and class VIII with high categories. Third, the effect of integrated science modules based on learning many material are high.